Kortárs szövegek tanítása felső tagozaton - Gombos, Péter (Studia Litteraria, 2019)
In the first part of my study I would like to prove that our way of teaching literature has moved in the wrong direction in the last few decades. As a result, our adolescents have a rather distorted picture about literature, and they lack reading experience, and the lighthearted debates, talks that would come from them. In my writing I attempted to draw attention to contemporary texts that I have already (successfully) used during my teaching practice, but are mainly absent from literature lessons. I intentionally avoid the genre of novel – evading the discussion about compulsory readings –, and I mainly focus on contemporary poems, short stories and lyrics. Although I offer several methodological ideas, I intended to share thought-provoking questions, tasks and games rather than lesson plans.